2008
DOI: 10.1007/s11427-008-0146-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of astaxanthin and its esters in the mutant E1 of Haematococcus pluvialis and other green algae by HPLC with a C30 column

Abstract: A gradient reversed-phase high-performance liquid chromatography (HPLC) method using a C30 column was developed for the simultaneous determination of astaxanthin, astaxanthin monoesters and astaxanthin diesters in the green algae Chlorococcum sp., Chlorella zofingiensis, Haematococcus pluvialis and the mutant E1, which was obtained from the mutagenesis of H. pluvialis by exposure to UV-irradiation and ethyl methanesulphonate (EMS) with subsequent screening using nicotine. The results showed that the contents o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 32 publications
3
25
1
Order By: Relevance
“…Therefore, astaxanthin in nature is either conjugated with proteins or esterified with one or two fatty acids to form monoester and diester forms [8,11]. In H. pluvialis, astaxanthins exist mainly as various astaxanthin esters formed by combining various fatty acids with different isomers of astaxanthin [6].…”
Section: Astaxanthin Profiles In Microalgaementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, astaxanthin in nature is either conjugated with proteins or esterified with one or two fatty acids to form monoester and diester forms [8,11]. In H. pluvialis, astaxanthins exist mainly as various astaxanthin esters formed by combining various fatty acids with different isomers of astaxanthin [6].…”
Section: Astaxanthin Profiles In Microalgaementioning
confidence: 99%
“…Peng et al [11] showed that the green microalga C. zofingiensis had a remarkably higher percentage of astaxanthin diesters in comparison with H. pluvialis with a higher percentage of astaxanthin monoesters. The esters of astaxanthin and adonixanthin, and free canthaxanthin were the major carotenoids in the alga Chlorococcum cells [3].…”
Section: Astaxanthin Profiles In Microalgaementioning
confidence: 99%
“…Other methods are based on conjecture. For example, in 2008 Peng and Xiang [15] analyzed the AM from green algae by HPLC using β-carotene as a standard. However, the inference was solely based on the higher polarity of AM than that of β-carotene.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, astaxanthin in nature is either conjugated with proteins or esterified with one or two fatty acids to form monoester and diester forms, producing an array of colors in different organisms 14,16 . It is the chromophore in the blue, green, and yellow pigments of lobsters.…”
Section: Different Chemical Forms Of Astaxanthinmentioning
confidence: 99%
“…In the astaxanthin molecule,each double bond from the polyene chain may exist in two configurations as geometric isomers cis or trans 13,15,16 . Most carotenoids found in nature are predominantly all trans-isomers 12,13 .…”
Section: Different Chemical Forms Of Astaxanthinmentioning
confidence: 99%